1991
DOI: 10.1021/ef00027a016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supercritical fluid solvent density on benzyl phenyl ether pyrolysis: indications of diffusional limitations

Abstract: The influence of supercritical solvent density on the pyrolysis of benzyl phenyl ether (BPE) in tetralin and supercritical toluene is interpreted in terms of transport limitations. Reaction at varying toluene densities highlighted the transport dependence of the BPE fission rate constant. The conversion of BPE decreased from 0.55 to 0.15 as the toluene density increased from 0.0 to 0.75. The yield and selectivity of BPE rearrangement products were also density dependent. These results were explained and modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Contributions for the latter three effects were evaluated. These investigators also examined the influence of density on reactions in SCFs ( Wu et al, 1991~). They showed that the conversion of benzyl phenyl ether decreased with increasing solvent (toluene) density, as shown in Figure 2'7.…”
Section: Aiche Journalmentioning
confidence: 99%
“…Contributions for the latter three effects were evaluated. These investigators also examined the influence of density on reactions in SCFs ( Wu et al, 1991~). They showed that the conversion of benzyl phenyl ether decreased with increasing solvent (toluene) density, as shown in Figure 2'7.…”
Section: Aiche Journalmentioning
confidence: 99%
“…This effect is predominantly observed in supercritical water, but has been invoked for reactions in subcritical water to rationalize the change in reaction pathways with different solvents or with increasing water density. [28] In the same way oligomer formation could potentially be suppressed, as the solvent cage would hinder diffusion of the sodium phenolate ion pair and thus suppresses formation of a carbanion.…”
mentioning
confidence: 99%
“…Hence, the reaction of a model compound containing α-O-4 bond can be of fundamental importance in understanding selective cleavage of ether bonds. In this respect, benzyl phenyl ether (BPE), which has an ether bond similar to α-O-4 bond without other functional groups, can be the simplest model to indirectly predict α-O-4 bond cleavage [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%